The towns of death : pogroms against jews by their neighbors - Tryczyk, Mirosław (2021)
I: How history was written – II: Nationalism in interwar Poland - an ideological outline – III: Jedwabne – IV: Radziłów – V: Wąsosz – VI: Szczuczyn and the vicinity – VII: Goniądz – VIII: Rajgród – IX: Kolno – X: Suchowola – XI: Brańsk – XII: Jasionówka – XIII: Chajim Nachman Bialik The City of Slaughter (excerpt) – XIV: Conclusions